Investigation of the inhibition effect of 1,2,3,4,6-pentagalloyl-β-D-glucose on gastric cancer cells based on a network pharmacology approach and experimental validation - Bi, Jing-hui; Jiang, Yu-han; Ye, Shi-jie; Wu, Min-rui; Yi, Yang; Wang, Hong-xun; Wang, Li-mei (Frontiers in Oncology, 2022)
Background: Gastric cancer(GC) is characterized by high global incidence and is the third leading cause of cancer-related mortality. 1,2,3,4,6-Pentagalloyl-β-D-glucose (β-PGG) has various pharmacological activities, and several studies have explored its anticancer role in various cancer types. The mechanism of β-PGG in inhibiting gastric cancer has not been elucidated. Purpose: The present study sought to explore the potential targets and mechanism of β-PGG against GC using network pharmacology approach combined with in vitro studies. Methods: PharmMapper software was used to predict potential targets of β-PGG, and GeneCards database was used to identify GC related genes. PPI analysis of common genes was performed using STRING database. The potential regulatory mechanism of β-PGG in GC was explored by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Effects of β-PGG on genes and proteins were evaluated by CCK-8 assay, cell cycle analysis, apoptosis assay, molecular docking, real time fluorescence quantification polymerase chain reaction (qRT-PCR) and western blot to verify the role of β-PGG in gastric cancer. Results: Eight hub genes implicated in cell cycle progression and apoptosis were identified in this study. Cancer-related signaling pathways were identified using Cytoscape tool. The findings showed that the genes were associated with significant enrichment of p53 signaling pathway. CCK-8 assay showed that β-PGG inhibited proliferation of GC cells. Cell cycle and apoptosis experiments showed that β-PGG induced cell cycle arrest and apoptosis of gastric cancer cells., qRT-PCR and western blot analysis showed that β-PGG played an anti-tumor role by modulating p53 signaling pathway. Conclusion: In the present study, the target and mechanism of β-PGG against gastric cancer was verified. The findings indicate that β-PGG is potential novel drug for treatment of GC.